2021
DOI: 10.3390/genes12091372
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Associated Manifestations in Pediatric Inflammatory Bowel Diseases

Abstract: Inflammatory bowel diseases (IBDs) are chronic relapsing inflammatory conditions of the gastrointestinal tract, encompassing Crohn’s disease (CD), ulcerative colitis (UC) and inflammatory bowel disease unclassified (IBD-U). They are currently considered as systemic disorders determined by a set of genetic predispositions, individual susceptibility and environmental triggers, potentially able to involve other organs and systems than the gastrointestinal tract. A large number of patients experiences one or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
(213 reference statements)
0
1
0
Order By: Relevance
“…The authors suggested an accurate screening and monitoring of thyroid function and autoimmunity to improve clinical practice and healthcare in children and adolescents with genetic syndromes. In the narrative reviews, Ferrari and Stagi reported the current literature regarding the genetic, immune, and environmental factors as the possible underlying mechanism of autoimmunity in individuals with Down syndrome [ 7 ]; Ben-Skowronek presented an update on IPEX syndrome making the knowledge of the genetics fundamental to introducing novel treatment methods in that pathology [ 8 ]; Roszkowska et al presented actual knowledge relative to the pathogenesis of Sjogren’s Syndrome, considering the role of innate immunity, adaptive immunity, and genetics [ 9 ]; and finally, Cucinotta et al presented an updated overview on the available evidence concerning the etiology (with genetic pattern), pathogenesis, and clinical presentation of pancreatic involvement in pediatric inflammatory bowel diseases [ 10 ].…”
mentioning
confidence: 99%
“…The authors suggested an accurate screening and monitoring of thyroid function and autoimmunity to improve clinical practice and healthcare in children and adolescents with genetic syndromes. In the narrative reviews, Ferrari and Stagi reported the current literature regarding the genetic, immune, and environmental factors as the possible underlying mechanism of autoimmunity in individuals with Down syndrome [ 7 ]; Ben-Skowronek presented an update on IPEX syndrome making the knowledge of the genetics fundamental to introducing novel treatment methods in that pathology [ 8 ]; Roszkowska et al presented actual knowledge relative to the pathogenesis of Sjogren’s Syndrome, considering the role of innate immunity, adaptive immunity, and genetics [ 9 ]; and finally, Cucinotta et al presented an updated overview on the available evidence concerning the etiology (with genetic pattern), pathogenesis, and clinical presentation of pancreatic involvement in pediatric inflammatory bowel diseases [ 10 ].…”
mentioning
confidence: 99%